The replacement of dysfunctional sensors based on the digital twin method during the cutter suction dredger construction process. (15th February 2022) - Wang, Bin; Fan, Shidong; Chen, Yong; Zheng, Liangyan; Zhu, Hanhua; Fang, Zhenlong; Zhang, Min
Highlights: The CSD can operate continuously even though the key sensor fails during construction. All CSD sensors have a digital twin backup. The Filter method computes less expensive than the Wrapper and Embedded methods with the same accuracy in the CSD data set. A sensor association digital twin network is established based on the stacking generalization model. Abstract: In practice, the construction environment of the cutter suction dredger (CSD) is inclement, which results in a high frequency of the key parameter sensor failure. If the key parameter data is missing or false, it will affect the continuity of the construction. This paper proposed a sensor network regression prediction method based on the "Digital Twin" to establish a correlated model between the key sensor and other highly reliable sensors in the CSD construction. The stacking model is trained by learning the CSD construction data that can synchronously calculate any key parameters when the dredger is running. The proposed method is validated on the "Changshi 12" CSD construction case. The results indicate that the method has high prediction accuracy and computes less expensively. Thus, the proposed method could better solve the problem of construction discontinuity caused by key sensor failure.